KONTRIBUSI METODE QUANTUM LEARNING TERHADAP HASIL BELAJAR SISWA SD SWASTA ETISLANDIA MEDAN - Parhusip, R.LHolmes; S, Hartono; Mendrofa, Yason; Heryanto, Heryanto; Barus, Juniar Ivana; Aswar, Rismalia; Nola, Feby (Universitas Asahan, 2024)
Education is carried out in a planned and systematic manner so that educational goals can be achieved in accordance with expectations through effective and efficient learning activities. Learning activities starting from the planning, implementation and assessment stages of the role of the tasks carried out by teachers are very complex, teachers who design and select materials, learning resources and learning media. Teachers are role models and main role models for students as well as models for their students. Therefore, a teacher must have Pedagogic competence, Professionalism, Personality, Social and experience, and noble character in himself which is part of his life, personality competence is also related to personal character that a teacher must have must be able to be a role model for his students and be able to educate. To overcome this, it is necessary to apply a learning model that inculcates students' interest and sitimulus in learning and there needs to be activeness from educators and students must be friendly, attentive and vice versa, students must also be polite, respect each other. The learning model used by teachers during learning activities in the classroom will optimize and maximize the success of achieving learning objectives and increase learning outcomes and students' learning interests for good learning outcomes for social studies students. Learning is a stage of change in all relatively sedentary individual behaviors as a result of experiences and interactions with the environment involving cognitive processes. Keywords: Quantum Learning Method, Audio Visual, Learning Outcomes